It was the best of times, it was the worst of times : understanding the relationship of hassles and mood in New Zealand elite athletes : thesis submitted in partial fulfilment of the requirements for the degree of Master of Health Science, Psychology, Massey University - Winther, Sara H. (Massey University, 2023)
Elite athletes pursuing a career in high performance sports face numerous hassles that can potentially lead to depression. In recent years, research on athlete mental health has gained momentum, driven by increased awareness of the challenges associated with this environment. However, there remains a dearth of published research on the mental health of elite athletes in New Zealand. A cross-sectional repeated measures online survey was available to athletes 18 years or older from 14 different sports disciplines associated with the High Performance Sport New Zealand athlete support program. Information was gathered on sport-specific challenges along with daily hassles and depression symptoms. Statistical analysis was performed to explore hypothesised group differences and relationships amongst constructs. In addition, a comparison to a study in 2015 was conducted. A total of 126 elite New Zealand athletes were included in the final analysis. Elite athletes experiencing symptoms consistent with depression were similar to rates seen in 2015, with 21.4% meeting the criteria for moderate symptoms consistent with depression. From this, 12.7% met the criteria for major symptoms consistent with depression, an increase from 2015. Current athletes showed a significant increase in hassles severity compared to 2015; however, this was not seen in the frequency of hassles. The daily hassles that received the highest endorsements were "rising prices of goods," followed by "troubling thoughts about the future," and "not getting enough sleep". The frequency and severity of hassles were found to be significant predictors of symptoms consistent with depression after controlling for demographic and sport-specific variables. Athletes who competed as individuals were significantly associated with increased hassles and had a 6.8 times increased risk of experiencing symptoms consistent with depression. Athletes considering retirement or soon to retire had a significantly increased frequency of hassles. Males were associated with increased severity of hassles. Athletes younger than 25 compared to those over 25 were significantly associated with symptoms consistent with depression. The findings indicate that although the overall incidence of symptoms consistent with depression has stabilised since 2015, individuals who exhibit these symptoms are experiencing them more severely, which is a cause for concern. The lack of an overall increase could be attributed to strategies implemented due to results from the 2015 study. These current findings highlight the relationships between hassles and symptoms consistent with depression; however, the study does not illuminate other factors. It suggests that the mental health of New Zealand elite athletes has remained consistent over the past 7 years and speaks highly to current mechanisms in place to support elite athletes. It would be beneficial to repeat this study in 2027, 1 year prior to the Olympic Games in Los Angeles, to enhance our understanding of this unique group and allow findings to inform future mental health strategies.
Figures 2, 3 & 5 are reproduced with permission.
Keywords: depression; daily hassles; stress; mental health; elite athletes; New Zealand; high performance sport; 520304 Health psychology